(untitled) (Research, Society and Development, 2025)
Heart failure (HF) is a multifactorial syndrome that predominantly affects the elderly and stands as one of the leading causes of hospitalization and death in Brazil. This study aims to analyze and compare the epidemiological profile of patients hospitalized with HF in the states of Paraná and Santa Catarina. This is an epidemiological, observational, and descriptive study based on time series analysis, conducted using secondary data extracted from DATASUS. The analysis revealed that most hospitalized patients were over 60 years old, predominantly female, and of white race/color, reflecting trends already observed at the national level. The results indicated a higher average hospitalization rate in Paraná (17.86 per 10,000 inhabitants) compared to the state of Santa Catarina (12.25 per 10,000 inhabitants), with a statistically significant difference (p=0.000002, t=-6.47). Furthermore, a slight recovery in hospitalization rates was identified between 2022 and 2024, following a sharp decline during the COVID-19 pandemic. It is evident that regional inequalities and the demographic profile of patients directly influence hospitalization and mortality rates due to HF, highlighting the need for targeted public policies and more effective prevention strategies to address this growing public health challenge.